2021
DOI: 10.21037/sci-2020-049
|View full text |Cite
|
Sign up to set email alerts
|

Literature review of cancer stem cells in oral lichen planus: a premalignant lesion

Abstract: Objective: As there is no review study about cancer stem cells (CSCs) involved in the pathogenesis of oral lichen planus (OLP), for the first time we review the role of these cells in OLP and this hypothesis may be a clue for the evaluation of the premalignancy of OLP.Background: Cellular mediated immune responses are the main etiopathogenesis in OLP and it is a potentially premalignant lesion. One of the factors proposed in the pathogenesis of OLP and the comparable trend of this autoimmune disease to squamou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Previous studies have suggested that cancers are organized as a cellular hierarchy of various populations of cancer cells, and the hierarchy is maintained by a small subset of cancer cells, called CSCs [ 33 , 34 ]. CSCs have stemness and are also called cancer-initiating cells [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 ]. CSCs were identified for the first time in 1997 by Bonnet and Dick in a patient with acute myeloid leukemia [ 46 ].…”
Section: Cscs In Osccmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that cancers are organized as a cellular hierarchy of various populations of cancer cells, and the hierarchy is maintained by a small subset of cancer cells, called CSCs [ 33 , 34 ]. CSCs have stemness and are also called cancer-initiating cells [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 45 ]. CSCs were identified for the first time in 1997 by Bonnet and Dick in a patient with acute myeloid leukemia [ 46 ].…”
Section: Cscs In Osccmentioning
confidence: 99%
“…CSCs have also been shown to play important roles in the development and progression of OSCC [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. It is reported that only a small percentage of the cell population contributes to the development of OSCC, and this population has properties corresponding to those of CSCs [ 31 , 40 ].…”
Section: Cscs In Osccmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The disease is considered as premalignant lesion with rare potential of malignant transformation. 3 T-lymphocytes infiltration in the basal cell layer of the epithelium and cytoid bodies are characteristic histopathologic features of the disease. 2 Genetic malformations and epigenetic mechanisms as microRNAs may have a rule in these changes.…”
Section: Introductionmentioning
confidence: 99%
“…The malignancy mechanism of OLP is still unknown. However, a factor proposed in the pathogenesis of OLP are cancer stem cells, which are increasing in atrophic-erosive clinical forms compared to reticular ones [ 18 ]. To date, there is no curative treatment for OLP.…”
Section: Introductionmentioning
confidence: 99%